STUDENTS’ READING HABIT AT THE FOURTH SEMESTER OF ENGLISH LANGUAGE EDUCATION, FKIP-UIR - Clara Angelica; Andi Idayani; Betty Sailun (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
During the COVID-19 pandemic, the learning process is carried out online and students spend a lot of time at home with the phone. Therefore, there are so many types of e-books that you can look for to read in your spare time. This research aims to find out the students' reading habit in the fourth semester of English Language Education, FKIP-UIR. This research used the descriptive qualitative method. The sample of this research was used purposive sampling. The research sample was 43 of class 4B at English Language Education of FKIP UIR. This study found that students' reading habits were categorized as positive. Almost all students have a good attitude toward reading. Then, most students enjoy reading ebooks and do not feel annoyed when asked to read e-books. Meanwhile, students also have positive book reading. Students have favorite types of e-books to read and read e-books quite often. Furthermore, students also have positive time spent on reading both in academic and non-academic. Finally, students also get positive motivation in reading, and students get motivation from their families and lecturers in the academic field to read e-books because reading can improve achievement. on the other hand, the researcher found one indicator of reading habits to get negative results. The indicator is reading frequency. Most students said they did not often visit the web for online reading resources as well as students did not often read e-books because they did not like reading and preferred listening to reading.